Clinical and pathomorphological parameters of brain death: from the origins of the concept to its use in organ transplantation - V. O. Tumanskyi; L. M. Tumanska (Zaporozhye State Medical University, 2020)
The criteria for brain death (BD), the parameters of their clinical and pathomorphological determination and use in organ harvesting for transplantation are being clarified in different countries to date. Objective: analysis of the formation and clinical and pathological characteristics of brain death. The review provides retrospective analysis of the formation and improvement of the medical concept of BD: the concepts of "death of the whole brain" (including the brain stem) and "death of the brain stem". Based on our own data, the main pathomorphological forms of BD are described (total necrosis of the brain, subtotal necrosis of the brain stem and cerebellum), their development mechanisms, and diagnostic pathological parameters. It has been established that the main criterion for the development of human biological death, which determines irreversible cardiac arrest and the impossibility of restoring spontaneous respiration, are irreversible destructive changes in the nuclei of the pons and medulla oblongata, which make up the cardio-respiratory center that regulates heart rate, vascular tone and blood pressure, and generating rhythm and breathing patterns. The modern standards of clinical diagnosis of BD and their real application in different countries during organ transplantation, as well as the prerequisites for the revival of the concept of "circulatory death" in the era of organ transplantation are highlighted. Conclusions. The applied three standards of human death have insufficiently studied medical aspects and unresolved ethical problems.